2015
DOI: 10.1007/s00429-015-1171-z
|View full text |Cite
|
Sign up to set email alerts
|

Prss56, a novel marker of adult neurogenesis in the mouse brain

Abstract: Adult neurogenesis in the mammalian brain is restricted to specific regions, such as the dentate gyrus (DG) in the hippocampus and the subventricular zone (SVZ) in the walls of the lateral ventricles. Here, we used a mouse line carrying a knock-in of Cre recombinase in the Prss56 gene, in combination with two Cre-inducible fluorescent reporters (Rosa26 and Rosa26 ), to perform genetic tracing of Prss56-expressing cells in the adult brain. We found reporter-positive cells in three neurogenic niches: the DG, the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

7
52
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 33 publications
(59 citation statements)
references
References 70 publications
7
52
0
Order By: Relevance
“…The presence of γ tanycytes was also demonstrated in the mouse median eminence (Miranda‐Angulo, Byerly, Mesa, Wang, & Blackshaw, ). Tanycyte‐like cells in the arcuate nucleus parenchyma were described by Jourdon et al () as cells having tanycyte‐like processes, elongated morphology and positive for genes characteristic of tanycytes including vimentin, nestin, and Sox2. They demonstrated that at least some of these cells are Prss56 ‐expressing α2 tanycytes that migrated into the parenchyma (Jourdon et al, ).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…The presence of γ tanycytes was also demonstrated in the mouse median eminence (Miranda‐Angulo, Byerly, Mesa, Wang, & Blackshaw, ). Tanycyte‐like cells in the arcuate nucleus parenchyma were described by Jourdon et al () as cells having tanycyte‐like processes, elongated morphology and positive for genes characteristic of tanycytes including vimentin, nestin, and Sox2. They demonstrated that at least some of these cells are Prss56 ‐expressing α2 tanycytes that migrated into the parenchyma (Jourdon et al, ).…”
Section: Methodsmentioning
confidence: 99%
“…While such obvious clues were not found, we came upon a unique expression pattern, that of Prss56 , a trypsin‐like serine protease (Nair et al, ), which is expressed specifically in neural stem/progenitor cells in the adult and embryonic mouse brain, including tanycytes (Jourdon et al, ). Reporter expression in Prss56 Cre/+ , Rosa26 tdTom/+ mice labels tanycytes, but only a fraction of them in a seemingly random distribution, as well as tanycyte‐like cells in the hypothalamic parenchyma that appear to be former tanycytes that translocated their soma into the parenchyma (Jourdon et al, ). Based on this unusual pattern, we hypothesized that Prss56 is expressed transiently in mouse tanycytes, and therefore, a potential candidate for a variably expressed gene that correlates with Pomc in rat tanycytes.…”
Section: Introductionmentioning
confidence: 99%
“…In lineage-tracing experiments using a Cre/lox system in which recombinase were expressed in tanycytes under the control of promoters, such as nestin (Lee and Blackshaw, 2012), glast (Robins et al, 2013), fgf10 (Haan et al, 2013), and prss56 (Jourdon et al, 2015), their role as neural stem cells was confirmed. In these transgenic mice, the constitutive expression of a reporter gene facilitates tanycyte tracking over time.…”
Section: Tanycytes As Hypothalamic Neural Precursor Cells (Npcs)mentioning
confidence: 97%
“…Notably, although specific marker genes (or combinations of marker genes) are used to roughly separate tanycyte subtypes, many genes exhibit a gradient, rather than a clear-cut distribution across tanycyte subpopulations which are consistent with the notion that tanycytes may be composed of continuous cell trajectory with transition zones between different subtypes. Recently two new markers UGS148 and Prss56 have been identified and found to be enriched in tanycytes [18,19]. …”
Section: Tanycyte Genetic Markersmentioning
confidence: 99%